2019
DOI: 10.4103/jfmpc.jfmpc_98_19
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum of renal disease in hospitalized HIV/AIDS patients: A teaching hospital experience

Abstract: Background: Renal involvement in HIV patients is relatively common and quite broad. However, despite an increasingly large number of HIV patients in Asia, systematic studies of renal involvement are lacking. Objectives: The study was carried out to delineate the clinical spectrum of renal disease in HIV/AIDS patients hospitalised in a tertiary care centre. Patients and Methods: A total of 510 consecutive hospitalised HIV/AIDS with age >18year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
(50 reference statements)
2
4
0
Order By: Relevance
“…Consistent with the tubular injury of HIVAN [3,4], it has been reported that sodium wasting is common in hospitalized HIV/AIDS patients in Chinese [19], European descent [20], and Indian [21] populations. However, the role of Vpr in the tubular histopathology of HIVAN is not well-characterized.…”
Section: Introductionsupporting
confidence: 53%
“…Consistent with the tubular injury of HIVAN [3,4], it has been reported that sodium wasting is common in hospitalized HIV/AIDS patients in Chinese [19], European descent [20], and Indian [21] populations. However, the role of Vpr in the tubular histopathology of HIVAN is not well-characterized.…”
Section: Introductionsupporting
confidence: 53%
“…The graph shows a down ward trend, the relationship between serum creatinine and sodium was weak negative Because the data points do not lie along a line, that was as the level of serum creatinine elevated there was a decrease of serum Na + among HIV infected patients. This agrees with the works done by Ramesh in 2017 and Verma & Singh in 2019 which reported elevated serum creatinine and decrease of sodium in HIV infected patients 8,11 . The study obtained statistically significant correlation between serum creatinine and potassium (P=0.01, r=0.22), with the graph showed an upward trend thus the association between serum creatinine and potassium was weak positive correlation means that as the level of serum creatinine elevated there was an increase of serum K + among HIV infected patients.…”
Section: Correlation Between Serum Creatinine and Sodiumsupporting
confidence: 93%
“…The frequencies of normal and abnormal serum creatinine levels, the minimum, maximum, mean and standard deviation in males and females in study population were determined by descriptive statistical analysis as summarized in table 2. HIV/AIDS patients hospitalize in a tertiary care center of India, reported that Acute renal failure was seen in 15% and CKD was found in 13% of HIV patients furthermore with elevated serum creatinine 8,13 . The reason why creatinine elevated among HIV infected patients would be due to the effect of anti-retroviral therapy treatments because some of them have nephrotoxicity which harm the renal parenchyma cells and lead to alteration of organ in removal of waste product from the body.…”
Section: Determination Of Serum Creatinine Levels Among Hiv Infected ...mentioning
confidence: 99%
“…Previous studies were conducted on adult HIV patients. Among them are studies by Verma and Singh [22] in India (r = -0.26, P = 0.02) and Adedeji et al [23] in Nigeria (r = -0.228, P = 0.025). The difference in results may be due to differences in subject age, the greater number of subjects in the previous studies, and the various mechanisms possibly underlying kidney complications.…”
Section: Discussionmentioning
confidence: 99%